Accessibility approach to Web applications development: An Experimental Study - Bittar, Thiago Jabur; Lobato, Luanna Lopes; Fortes, Renata Pontin de Mattos (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2013)
Despite the number of studies available in the literature, about the use of accessibility during Web application development, there are some gaps related to lack of empirical results about it, and so, accessibility barriers are intrinsically present in the organizational culture. In order to contribute to the accessibility domain, we developed an approach used to provide support and facilitate the use of accessibility during Web applications development. In this paper, we presented the results identified through the use of such approach in a controlled experiment. In this sense, we could verify the benefits and drawbacks with the use of it, and so propose improvements for it. This experiment was carried out with the contribution of participants, which were divided in two groups. We understand that such scenario may not enable us to generalize our findings to a diversity of scenarios, however, this study could serve as an initial point towards validating our approach, and may serve to establish baseline values for future studies.